Heterobimetallic complexes composed of bismuth and lithium carboxylates as polyurethane catalysts – alternatives to organotin compounds. Issue 7 (26th March 2021) - Levent, Emre; Sala, Oliver; Wilm, Lukas F. B.; Löwe, Pawel; Dielmann, Fabian
Abstract : The bismuth-catalyzed urethane reaction is significantly accelerated by generating heterobimetallic mixtures of bismuth and lithium carboxylates. Abstract : Organotin compounds are important catalysts for the synthesis of polyurethanes consisting of aliphatic isocyanates and polyols. Due to their toxicity, however, it has been a long-standing goal to develop more environmentally benign catalysts. Bismuth octoates and neodecanoates are such well-known alternatives, but their catalytic activity is insufficient for many applications. Herein we show that the catalytic activity of bismuth carboxylates can be enhanced significantly by the addition of lithium carboxylates. Structural and spectroscopic results reveal the spontaneous formation of heterobimetallic complexes consisting of two bismuth and four lithium carboxylates that show dynamic behaviour in solution. The mechanism of the bismuth-catalyzed urethane reaction was elucidated in detail using quantum chemical calculations, paving the way for a rational catalyst design.